MENTAL HEALTH OF MEDICAL STUDENTS DURING WARTIME - Inshyna, Nataliia; Chorna, Inna (Eastern Ukrainian Medical Journal, 2026)
Introduction. Preserving the mental health of Ukrainians during wartime remains one of the most urgent challenges for the national healthcare system. Continuous monitoring of psychological well-being is essential for developing effective recovery strategies and fostering resilience, particularly among young people in medical education who are expected to provide care to others in the future.Objective. This study aimed to assess the impact of the war in Ukraine on the mental health of medical students at Sumy State University.Materials and Methods. The mental health status of the students was evaluated using the Goldberg General Health Questionnaire (GHQ-28), which measures four domains: somatic symptoms, anxiety and insomnia, social dysfunction, and depression. A total of 105 students (72 females and 33 males) aged 18–22 years participated in the anonymous survey conducted from May 2024 to January 2025. The study was conducted in accordance with the Declaration of Helsinki (World Medical Association, “Ethical Principles for Medical Research Involving Human Subjects,” 2013 revision). Statistical analysis was carried out using descriptive statistics with the Microsoft Open Value Subscription program.Results. The findings revealed that 85% of the respondents experienced a deterioration in mental health related to wartime stress. The most prevalent psychological disturbances were anxiety and insomnia (80%), followed by social dysfunction (65%) and somatic symptoms (60%). Depressive manifestations were observed in 11% of the participants. Female students demonstrated a higher vulnerability to stress and emotional distress than their male peers.Conclusions. Wartime conditions significantly affect the psychological well-being of medical students, compromising their academic performance and professional preparedness. To sustain effective learning and adaptation, it is crucial to provide targeted psychological support, implement mental health monitoring, and develop training programs focused on self-regulation and stress resilience in crisis environments.